2010
DOI: 10.1021/jm901379s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and QSAR of Quinazoline Sulfonamides As Highly Potent Human Histamine H4 Receptor Inverse Agonists

Abstract: Hit optimization of the class of quinazoline containing histamine H(4) receptor (H(4)R) ligands resulted in a sulfonamide substituted analogue with high affinity for the H(4)R. This moiety leads to improved physicochemical properties and is believed to probe a distinct H(4)R binding pocket that was previously identified using pharmacophore modeling. By introducing a variety of sulfonamide substituents, the H(4)R affinity was optimized. The interaction of the new ligands, in combination with a set of previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 33 publications
1
76
0
1
Order By: Relevance
“…3 and 4) as results from binary QSAR analysis using RPART [24] were evaluated for chance correlation [32,33], crosscorrelation between descriptors [33], and over fitting [34]. Since no evidence of those parameters was found in both decision trees resulted from the binary QSAR analysis using RPART [24], SBVS_2 and SBVS_3 were statistically valid to be used further in virtual screening campaigns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 and 4) as results from binary QSAR analysis using RPART [24] were evaluated for chance correlation [32,33], crosscorrelation between descriptors [33], and over fitting [34]. Since no evidence of those parameters was found in both decision trees resulted from the binary QSAR analysis using RPART [24], SBVS_2 and SBVS_3 were statistically valid to be used further in virtual screening campaigns.…”
Section: Resultsmentioning
confidence: 99%
“…Although SBVS_3 is slightly better than SBVS_2 (Table 1), employing multiple poses in SBVS_3 increases degree of freedom and could complicate the subsequent de novo design attempts compared to SBVS_2 [36]. Nevertheless, this success story offers possibilities to employ other supervised machine learning methods in post retrospective SBVS campaigns to optimize the predictive abilities [32,37].…”
Section: Istyastono Et Almentioning
confidence: 99%
“…1 revealed that Gram-positive bacteria were more susceptible towards the tested compounds than Gramnegative bacteria. The bis benzothiazolyl quinazolines (8) exhibited higher activity than bis benzoxazolyl quinazolines (7) and bis benzimidazolyl quinazolines (9). It was noticed that 8c and 8f having chloro and nitro substituent on the aromatic ring displayed greater activity particularly on Staphylococcus aureus.…”
Section: Biological Resultsmentioning
confidence: 99%
“…imidazol-2-yl) quinazoline-2,4-diamine (9) were obtained by treating 3 with 5 and 6, respectively (Chart 1). The 1 H-NMR spectra of 7a, 8a and 9a displayed a broad singlet at δ 9.32, 9.49 and at 9.12 ppm due to NH protons in addition to the signals of aromatic protons.…”
Section: And N2n4-di(1h-benzo[d]-mentioning
confidence: 99%
“…We also noticed that the conserved F1835.47 is positioned further inside the H4 binding site, compared to its position in the H3 binding site, making it more accessible for interactions with ligands. This observation can help the design of H4 selective antagonists, as shown previously [2,[83][84][85]. With the models of H3 and H4, SDM data and fragment hits in hand, we next turned to the docking, optimization and exploration of receptors binding sites followed by VS.…”
Section: Modelling Of Human H3 and H4 Receptorsmentioning
confidence: 95%